Literature review on shipyard productivity in Indonesia - Thaib Rizwan; Ayana Rizki; Umiralaska Salsabila; Muhammad Muhammad; Riyan Maulana; Makwiyah A Chaliluddin; Junaidi M Affan; Razali Thaib; Suhendrianto Suhendrianto; Yusrizal Muchlis (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The shipyard industry plays an important role in supporting fishing activities and efforts to fulfill animal protein for humans. It is an industry that has an orientation to produce a product in the form of a ship. There are two types of shipyards, which are offshore buildings and floating buildings - both are used to build new ships and repair old ships. Based on the level of technology used by the shipyard industry, it is divided into modern, traditional, and semi-modern shipyards. Its productivity can see the advantages and disadvantages of a shipyard to ensure this industry remains to exist. Several factors need to be taken into account to increase the shipyard productivity, including land or location, human resources, technology, and materials.Keywords:ProductivityShipyardTechnology